Large group portrait of teenage girls at Asilomar for a Y-Teens Conference - Crouch, Steve, 1915-1983 (photographer):::Creator::::::::::::
Large group portrait of teenage girls at Asilomar in 1952 for the Y-Teens Conference. 2nd Row from top: 13 from left Nancy Daubert 14 Mary Hule (both are from Morgan Hill. 3rd Row 2nd from right Muriel Waltz, Teen Age Director, San Jose 9 and 10 from left Yvonne Barcus - Campbell Mary Golen - Sunnyvale. Charlotte Huber, Carolyn Fry (both are from Campbell) Mercedes Portal - Santa Clara. Some of the girls in the first two rows are wearing a cross between a Japanese kimon and a Hawaiian holoku dress.